Web-Based E-Commerce Design Of Customer Relationship Management Method At Coffee Ratio Shop - Alamsyah, Reza (Cattleya Darmaya Fortuna, 2022)
Toko Rasio Kopi, which sells specialty coffee products, does not yet have a specific sales and customer service strategy. Sales are made through promotions on Instagram, however, promotions are limited and information is only shared verbally. The design of the E-Commerce information system was built using the PHP programming language. The design of this web-based information system is able to assist in terms of reporting sales transaction data, ordering goods, and invoices for consumer purchases. By using E-commerce sales, the data storage process becomes more accurate, the promotion process can be faster so that the response to sales will be faster too.Rasio coffee shop sales information system can provide the latest product information, discounts, and other promotions with Customer Relationship Management (CRM) techniques. Customers can easily purchase products online by using Customer Relationship Management (CRM) on the sales information system at the ratio store.